Diseño e implementación de un horno basculante para fundir aluminio - Coronel Subía, Mario Andrés (2019)
The incorrect use of thermal materials at “FUNDICIONES SANGUCHO” company caused a waste of time for the oven to reach an ideal temperature to be more than necessary, for this, through the analysis of its variables, a design and construction was designed and built. Tilting furnace to reduce the time in the smelting process, which is used as a tool for the fusion of aluminum scrap at "FUNDICIONES SANGUCHO" company. In the designing of the tilting furnace to melt aluminum, the thermal fluxes of the heat losses to the medium, the amount of energy needed for the smelting process. The internal capacity of the oven, the calculations for the structure to support its weight and The cost of diesel consumption in the smelting of a 250kg load of aluminum, which is the amount that the company requires to complete its work in a normal working day. With the implementation of the tilting furnace, the heating time of this was improved. The bucket heating was eliminated and the manual direct pouring system was added, which speeds up the dismantling process of the finished parts, obtaining twice the production at the same time of work, since this work was carried out with an oven built in an artisanal way. The use of burned oil as the fuel part of the oven was also eliminated, since it is a highly toxic, dangerous and difficult to store product. Due to the standars with which it is regulated, through the comparison made between diesel and burned oil it was determined that the heat capacity of diesel is much better and this also allows saving time at the time of smelting of aluminum without affecting the costs of fuel.